Die advertensie - Muller, Frederick Johannes (Afrikaans and Netherlandic Studies, 2016)
"When does a language die?" This question leads to the central, overarching theme explored in the novel. The protagonist is a naive twenty-something who runs a boutique advertising agency in the bustling heart of Cape Town. As a published author he has a passion for Afrikaans literature but he knows that due to the socio-economic climate of the current postapartheid South Africa, making a career out of his passion, is futile. It is this reality that is investigated in the text, posing a secondary question: Can a passionate, gifted individual follow his or her artistic ambitions in South Africa's current socio-economic environment? The story unfolds with a car crash that leaves the protagonist paralyzed and dying in the middle of nowhere. With this scene, the protagonist becomes a metaphor for the Afrikaans language - a language paralyzed by its historical baggage, dying in the middle of nowhere (the southern tip of Africa). The protagonist also represents the passionate, young artists and writers who naively dream of achieving artistic success and saving the language. A young girl stumbles upon the lead character in this deserted landscape (almost as one would stumble upon a new piece of literature). The girl's father is "out of town", and therefore can't help. So, she tries to save him herself, giving him nourishment and accompaniment. The missing father figure, or more specifically, the missing leader figure, is also fundamental to the theme. It intensifies the concept that the burden is upon the younger generation to save themselves, their language and their culture. The plot of the novel drives this theme. The protagonist is given the chance to save himself, his family and his language - everything he holds dear - by an opportunity created by a business tycoon. This character is depicted as the quintessential leader figure. He has the desire to create a long-lasting legacy by saving the language and he has the financial means to see it through. He briefs the protagonist as well as other agencies to conceptualize a marketing campaign that will ensure the survival of the Afrikaans language for generations to come. In the final chapter, the protagonist dies, not being able to save himself, his family, or his language. The young girl that discovered him, now buries him with his notebook (which is filled with his literary writings sporadically featured throughout the text). The metaphor is thus that as he (the young, passionate writer) dies, the language dies. The theme's crescendo is reached in the final three sentences of the novel, where it is professed that the Afrikaans language will not die some unforeseeable time in the future, but that the language is in fact already dead. And there is nothing the passionate, naive young artists can do to save it. By dying, the protagonist himself becomes the concept of his marketing campaign. He becomes the billboard, the advertisement (Die Advertensie), for a language that cannot be saved.